Burn - Barr, Nevada (New York : Minotaur Books, 2010)
"Anna Pigeon, a Ranger with the National Park Service...decides to go stay with an old friend from the Park Service, Geneva, who works as a singer at the New Orleans Jazz National Historic Park...it will take all of Anna's skills learned in the untamed outdoors to navigate the urban jungle in which she finds herself..." --inside cover.
"An Anna Pigeon novel"--Jacket.
Keywords: Pigeon, Anna (Fictitious character) -- Fiction; Women park rangers -- Fiction; New Orleans (La.) -- Fiction; Mystery fiction